2012
DOI: 10.1016/j.gloplacha.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Plume-induced dynamic instabilities near cratonic blocks: Implications for P–T–t paths and metallogeny

Abstract: et al.. Plume-induced dynamic instabilities near cratonic blocks: implications for P-Tt paths and metallogeny. Global and Planetary Change, Elsevier, 2012, 90-91, pp.37-50. 10.1016/j.gloplacha.2011 ÔØ Å ÒÙ× Ö ÔØ Plume-induced dynamic instabilities near cratonic blocks: Implications for P-T-t paths and metallogeny This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…The intrinsic linkage between horizontal and vertical motions illustrated by these models suggests that the coeval changes at approximately 90 Ma and 30 Ma in the South Atlantic spreading rates (Figure ) and uplift of the southwest African continental margin are geodynamically linked to one another. The interaction between in‐plane stresses in the lithosphere and thermal convection in the mantle has been investigated by recent three‐dimensional thermomechanical models using realistic lithospheric rheologies and predict complex patterns of short‐wavelength deformation of a brittle crust overlying a ductile mantle lithosphere [ Burov , ; Guillou‐Frottier et al, ; Burov and Gerya , ; Koptev et al, ]. This work offers the interesting possibility of a regional, long‐wavelength mechanism of uplift, like mantle flow, causing quite local deformation at the surface, and would explain why we observe both regional and local signals of tectonic activity within Southern Africa during the mid‐Cretaceous.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic linkage between horizontal and vertical motions illustrated by these models suggests that the coeval changes at approximately 90 Ma and 30 Ma in the South Atlantic spreading rates (Figure ) and uplift of the southwest African continental margin are geodynamically linked to one another. The interaction between in‐plane stresses in the lithosphere and thermal convection in the mantle has been investigated by recent three‐dimensional thermomechanical models using realistic lithospheric rheologies and predict complex patterns of short‐wavelength deformation of a brittle crust overlying a ductile mantle lithosphere [ Burov , ; Guillou‐Frottier et al, ; Burov and Gerya , ; Koptev et al, ]. This work offers the interesting possibility of a regional, long‐wavelength mechanism of uplift, like mantle flow, causing quite local deformation at the surface, and would explain why we observe both regional and local signals of tectonic activity within Southern Africa during the mid‐Cretaceous.…”
Section: Discussionmentioning
confidence: 99%
“…Morency et al [2002] found that, depending on the width of the cratonic block, it takes 50-750 Myr to convectively remove a 250 km thick cratonic root if the lithosphere has an equilibrium thickness of about 100 km, but the chemical heterogeneity of continental lithosphere and plume events was not considered in their study. Guillou-Frottier et al [2012] argued for several different plume-induced dynamical instabilities near the cratonic root to explain the P-T-t paths recorded by the metallogenic data from South Africa. These studies do not explicitly explore the role of compositional buoyancy and strengthening on cratonic mantle dynamics for a situation in which a plume impacts on the subcontinental root.…”
Section: Introductionmentioning
confidence: 94%
“…Guillou‐Frottier et al . [] argued for several different plume‐induced dynamical instabilities near the cratonic root to explain the P‐T‐t paths recorded by the metallogenic data from South Africa. These studies do not explicitly explore the role of compositional buoyancy and strengthening on cratonic mantle dynamics for a situation in which a plume impacts on the subcontinental root.…”
Section: Introductionmentioning
confidence: 99%
“…Insights from geodynamic models support the hypothesis that vertical stresses imposed at the base of the lithosphere by the vertical component of mantle flow will induce significant uplift (or subsidence for downwelling mantle) of the interior plateau [e.g., Gurnis et al, 2000;Moucha et al, 2008;Braun, 2010;Forte et al, 2010;Flament et al, 2014]. It is also significant that recent thermomechanical models that simulate the interaction between mantle convection and the overlying lithosphere suggest that brittle deformation of the upper crust at short-wavelength scales may also occur in tandem with longer wavelength (plume-induced) uplift of the lithosphere [e.g., Burov and Cloetingh, 2009;Guillou-Frottier et al, 2012;Cloetingh et al, 2013;Koptev et al, 2015]. In addition to deformation arising from these vertical stresses applied at the base of the lithosphere, horizontal stresses arising from plate boundary and plate kinematic changes may propagate significant distances and drive local, brittle deformation and reactivation of pre-existing structures within continental interiors [Daly et al, 1989;Janssen et al, 1995;Guiraud and Bosworth, 1997;Fairhead et al, 2013;Viola et al, 2012;Pérez-Díaz and Eagles, 2014;Salomon et al, 2014Salomon et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%